Adoption of Rainwater Harvesting Technology and Drip Irrigation Automation by Akur Muda Farmer Group, Ngaglik District, Sleman Regency, Yogyakarta (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The horticulture sector in Sleman Regency has great potential to be developed thanks to the fertile land at the foot of Mount Merapi. However, challenges of high-water availability and climate change, such as the El Nino phenomenon, hinder the growth and production of horticultural crops. Several technologies have been introduced and adopted to address these issues, including rainwater harvesting systems, drip irrigation, and the Internet of Things (IoT) for system automation. Implementing these technologies has resulted in significant adoption among young farmers, with 80% adopting rainwater harvesting systems, 35% drip irrigation, 15% IoT, and 10% adopting all three technologies together. Adopting these technologies is changing the mindset and behavior of young farmers, increasing their awareness and understanding of modern agricultural technologies. This facilitates more efficient and sustainable agricultural production and improves the quality and productivity of agricultural products. Thus, young farmers in Sleman Regency are a promising long-term investment in improving the quality of human resources in the agricultural sector, supporting their existence in the industrial era 4.0, and strengthening the sustainability of the agricultural system in the region.